Shaping Santri Character Through Muhadhoroh Activities at Alkarim Rasyd Islamic Boarding School, Kotabumi, North Lampung - Anita A; Wahyudi Hidayah (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Islamic boarding schools play a very important role, as a place for students to learn while carrying out their mission in spreading Islamic teachings. At the Al Karim Rasyd Islamic Boarding School, students are trained to develop their abilities and skills in preaching through muhadhoroh activities. The objectives of this study are 1) to understand the management of muhadhoroh activities at the Al Karim Rasyd Islamic Boarding School, 2) to explore the influence of muhadhoroh on the mental development of students, and 3) to examine the impact of muhadhoroh activities on the mental development of students. The method used in this study is a descriptive qualitative approach, with data collection techniques through interviews, documentation, observation, and data analysis carried out through the following steps: data reduction, data presentation, and drawing conclusions. The results of the study indicate that the management of muhadhoroh activities in shaping the mental development of students begins with planning that includes muhadhoroh training. The organization is carried out by assigning muhadhoroh officers in each class, the implementation of which includes opening, reading of holy verses of the Qur'an, greeting, sholawat, core (muhadhoroh), prayer, and closing, where supervision is carried out by the administrators, as well as evaluation of the results of the implementation of muhadhoroh activities. The formation of the mentality of students through muhadhoroh activities is influenced by supporting and inhibiting factors. Supporting factors include obligations and the existence of guidance from all administrators, while inhibiting factors are feelings of pessimism and shame that exist in students. Â